THE EXTINCTION LAW IN THE ORION NEBULA - PEIMBERT, M; COSTERO, R (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1970)
An average extinction law for the Orion Nebula is obtained by comparing emission line optical observations and continuum radio observations with theoretical computations for four regions in the Nebula. The derived law is abnormal and yields an R = 5.5 +/-
BOL OBS TONAN TACUB
Keywords: EXTINCTION, LAW, ORION NEBULA; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS